1993
DOI: 10.1029/92jd01917
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of surface heat and moisture fluxes over a prairie grassland: 4. Impact of satellite remote sensing of slow canopy variables on performance of a hybrid biosphere model

Abstract: Herein, we present the results of a series of numerical experiments using the Ex-BATS biosphere model, which is an adaptation of Dickinson's biosphere-atmosphere transfer scheme (BATS). These simulations are used to assess how the model performs when remotely sensed data are used to estimate three key canopy variables. These canopy variables, which effectively represent the slowly changing boundary conditions of a vegetated surface, consist of the total surface albedo, leaf area index, and the nondiurnally var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Modifications to the original model include a redesign of the radiation scheme, a more explicit treatment of the soil thermal properties, and a more flexible treatment of the various canopy variables. The original description of Ex-BATS can be found in the work of Smith et al [1993] and Crosson et al [1993]. The canopy albedo algorithm of Sellers [1985] has been since incorporated into the model.…”
Section: Description Of Biosphere-atmosphere Exchange Modelmentioning
confidence: 99%
“…Modifications to the original model include a redesign of the radiation scheme, a more explicit treatment of the soil thermal properties, and a more flexible treatment of the various canopy variables. The original description of Ex-BATS can be found in the work of Smith et al [1993] and Crosson et al [1993]. The canopy albedo algorithm of Sellers [1985] has been since incorporated into the model.…”
Section: Description Of Biosphere-atmosphere Exchange Modelmentioning
confidence: 99%
“…Resolution at satellite subpoint is about 1.1 km so that the area around each station covered by the spatial averaging process is approximately 11 km 2. Cloud subgrids were eliminated using a screening process [see Crosson et al, 1993]. After the screening procedure was applied, 30 daily overpasses form 1987 and 4 days from 1989 were obtained for the analysis.…”
Section: Surface and Satellite Datamentioning
confidence: 99%
“…budget, and to heat and moisture exchanges between the land surface and the atmosphere [e.g., Wetzel et al, 1984;Wetzel and Woodward, 1987]. Recently, a four-part paper by Smith et al [1992a], Crosson and Smith [1992], Smith et al [1993], and Crosson et al [1993] reported the development of a hybrid modeling approach in which satellite-derived estimates of various surface variables are used as boundary condition inputs within a detailed biosphere-atmosphere exchange model to diagnose surface heat and moisture fluxes. This study is a follow-up to the aforementioned study in which we use the same experimental version of the biosphere-atmosphere transfer scheme (Ex-BATS) [see Smith et al, 1993] to provide estimates of sensible heat fluxes during the First International Satellite Land Surface Climatology Project (ISLSCP) Field Experiment (FIFE) in 1987 and 1989.…”
mentioning
confidence: 99%
“…In practice, few of these models can be used at regional scales with remote sensing data because of the amount of vegetation and soils information required to evaluate the necessary parameters. Attempts at bridging this gap between having a physically-based robust model simulating the energy fluxes and remote sensing providing necessary information for determining key surface parameters in an operational mode have been successful to some degree Crosson et al, 1993). Two such approaches which appear to have great potential for estimating ET operationally are discussed below in some detail.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…None of the models explicitly address the issue of subpixel averaging (7). Preliminary studies (Crosson et al, 1993;Sellers et al, 1992) and some in progress using FIFE data suggest that issue 7 may be a significant problem at the 1 km scale but may average out at the 10 km scale (Norman & Divakarla, 1995). None of the current models addresses the issue of continuous surface fluxes even with clouds, but studies are in progress to combine the thermal IR remote sensing approaches discussed in this paper with mesoscale models, synoptic surface observations and microwave observations.…”
mentioning
confidence: 99%